Young Adults' Support for Adult‐Ratings for Movies Depicting Smoking and for Restrictions on Tobacco Magazine Advertising. Issue 4 (December 2013) - Choi, Kelvin; Fabian, Lindsey; Jansen, Jim; Lenk, Kathleen; Forster, Jean
Abstract Smoking images in movies and tobacco advertisements in magazines are influential on adolescent smoking behaviors, and restrictions of these advertising strategies can reduce the prevalence of adolescent smoking. We assessed young adults' level of support for adult ratings for movies depicting smoking and for restrictions on tobacco magazine advertising. Young adults from the U.S. Midwest were surveyed between 2010 and 2011 (n = 2, 622). We assessed their level of support for (a) adult‐rating all movies depicting smoking, and (b) restrictions on tobacco magazine advertising. Multivariate regression models were used to investigate the characteristics associated with higher level of support for these policies. Overall, 34 percent of the participants favored adult ratings for movies with smoking images, and 68 percent favored restrictions on tobacco magazine advertising. Characteristics associated with higher level of support differed somewhat by policy. Further educating young adults about the influence of smoking images in movies on adolescent smoking may be necessary to gain more support for the policy. With the majority supporting restrictions on tobacco magazine advertising, it may be possible to tighten these restrictions to further protect adolescents. Future research is needed to identify how tobacco control advocates can frame these issues to gain further public support.